2023
DOI: 10.3389/fpls.2023.1124536
|View full text |Cite
|
Sign up to set email alerts
|

Application of third-generation sequencing to herbal genomics

Abstract: There is a long history of traditional medicine use. However, little genetic information is available for the plants used in traditional medicine, which limits the exploitation of these natural resources. Third-generation sequencing (TGS) techniques have made it possible to gather invaluable genetic information and develop herbal genomics. In this review, we introduce two main TGS techniques, PacBio SMRT technology and Oxford Nanopore technology, and compare the two techniques against Illumina, the predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…As a gold standard for target identification, sequencing enables the capture of any nucleotide variation, enhancing the sensitivity of AGE to single-base differences. Additionally, advancements in sequencing technologies have streamlined the batch verification of large sample numbers ( Gao et al, 2023 ), particularly benefiting laboratories or professional institutions equipped with specialized DNA sequencers and technologists. Moreover, CRISPR-Cas12a contributes to AGE as a simple and on-site species identification method, which is especially important to meet the clinical, customs, and market needs for rapid fungal identification.…”
Section: Discussionmentioning
confidence: 99%
“…As a gold standard for target identification, sequencing enables the capture of any nucleotide variation, enhancing the sensitivity of AGE to single-base differences. Additionally, advancements in sequencing technologies have streamlined the batch verification of large sample numbers ( Gao et al, 2023 ), particularly benefiting laboratories or professional institutions equipped with specialized DNA sequencers and technologists. Moreover, CRISPR-Cas12a contributes to AGE as a simple and on-site species identification method, which is especially important to meet the clinical, customs, and market needs for rapid fungal identification.…”
Section: Discussionmentioning
confidence: 99%
“…While recent research suggested that genome-sized circular molecules are rare and mitogenomes with various isoforms are more common, this study found that 45.8% of mitogenomes in Caryophyllales exhibit a single circular structure. It is worth noting that more than a half of these single circular mitogenomes were obtained using Illumina sequencing with relatively short read lengths, which may not have captured the complete isoform information [20][21] . Therefore, further clarification of this issue may require more long-read sequencing data, comparative analysis and experimental evidence.…”
Section: Comparison Of Protein-coding Genes Of Mitogenomes In Polygon...mentioning
confidence: 99%
“…Therefore, the characterization and comparison of mitochondrial genomes (mitogenome) are highly significant and also hold great potential for revealing evolutionary relationships and the molecular identification of various organisms. Due to the rapid advancement of sequencing techniques, numerous mitogenomes of medicinal plants have been released [17][18][19][20] . They not only deepened our understanding toward the basic characteristics of the mitogenomes of medicinal plants [21][22] but also provided useful information for evolution history [23][24] and molecular identification research [25] .…”
Section: Introductionmentioning
confidence: 99%
“…In absence of specific provisions for spices and herbs in the European Union (EU) regulatory framework, the assessment of authenticity and purity needs to be aligned with relevant ISO standards. To evaluate these ISO criteria, several analytical methods with complementary outputs are implemented, ranging from high-performance liquid chromatography coupled to mass spectrometry for non-authorised synthetic dyes and chemical markers (such as piperine for pepper, Sing et al, 2022; ISO 11027:1993) to X-ray fluorescence spectroscopy for elements detection such as heavy metals (Feng et al, 2021) and DNA-based analyses to highlight the presence of undeclared species (Gao et al, 2023; Hoffman et al, 2021). Hence, several sophisticated frauds have been evidenced with multistep workflows (Garber et al, 2016; Ordoudi et al, 2017; Xu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%